HUBUNGAN TINGKAT STRESS DAN KONSUMSI MINUMAN MANIS TERHADAP KEJADIAN GIZI LEBIH PADA MAHASISWA PROGRAM STUDI GIZI PROGRAM SARJANA UPN VETERAN JAKARTA - Nanda Sherina Marsya Putri (2022)
Overnutrition is a pathological condition in which there is a fat accumulation that is higher than required. Students are in the early stages of adulthood with an age range of 18-25 years. Students who are overweight are those who have a Body Mass Index (BMI) of 23 - 24.9 kg/m (overweight) and 25 - 29.9 kg/m. The prevalence of overnutrition in the adult age group (>18 years) in Indonesia according to the 2018 Basic Health Research (Riskesdas) is 13.6% and obesity is 21.8%. The prevalence of overnutrition in the DKI Jakarta province was recorded at 15.6% and obesity at 29.8%. The prevalence of overweight in the province of West Java was recorded at 13.7% and obesity cases at 23%. This study aims to analyze the relationship between stress levels and consumption of sugary drinks on the incidence of overnutrition in undergraduate students of Nutrition Sciences UPN Veteran Jakarta. This research is quantitative research conducted with a cross-sectional study design which has a sample size of 64 respondents using a simple random sampling method which was carried out in June 2022. The results of the bivariate test with Spearman Rank showed that there was a relationship between stress levels (p = 0.002) with the incidence of overnutrition, but there is no relationship between the consumption of sugary drinks (p=0.220) with the incidence of overnutrition. The citizen is expected to be able to manage stress levels so that coping stress does not occur which causes overnutrition.